Penerapan Metode Analytical Hierarchy Process (AHP) Pada Desain Sistem Pendukung Keputusan Pemilihan Calon Penerima Bantuan Pangan Non Tunai (BPNT) Di Kota Palangka Raya - Jadiaman Parhusip (Universitas Palangka Raya, 2019)
Village/ward party in Palangka Raya is required to collect data of poor people who reserve the right to receive Non-Cash Food Aid (BPNT). Eventually, village/ward party is going to work together with the census officers of Social Protection Program of Central Statistics Body (BPS) in Palangka Raya. The decision process of the recipient candidates of BPNT in Palangka Raya requires a Decision Support System which offers consideration and evaluation to obtain more accurate data. The selection uses ten poor criteria of non-monetary variable include main income, possession status of a house to live, floor material of the house, wall material of the house, facility of drinking water, facility of lighting, fuel for cooking need, facility of defecation, final disposal of feces, and asset possession of household. The research used the Decision Support System with Analytical Hierarchy Process (AHP) method. The system was evaluated by two different methods which were black box testing and turing testing. The application assists to decide the alternative recipient of BPNT, manage data of candidates of recipient of BPNT and manage data of the recipient of BPNT which were selected from the recommendation result